Предмет:
МатематикаАвтор:
анонимУпростим выражения:
1)(с/d + (2 + d)/c) : (c + d)/d = (c * c + d * (2 + d))/(c * d) : (c + d)/d = (c ^ 2 + 2 * d + d ^ 2))/(c * d) * d/(c + d) = (c ^ 2 + 2 * d + d ^ 2))/c * 1/(c + d);
2)(k/(k + t) - 2 * k * t/(k ² - t ²) + t/(k - t)) : (t/(k - 1)) = (k * (k - t) - 2 * k * t + t * (k + t))/(k ^ 2 - t ^ 2) : (t/(k - 1)) = (k ^ 2 - k * t - 2 * k * t + t * (k + t))/(k ^ 2 - t ^ 2) : (t/(k - 1)) = (k ^ 2 - k * t - 2 * k * t + t * k + t ^ 2)/(k ^ 2 - t ^ 2) : (t/(k - 1)) = (k ^ 2 - 2 * k * t + t ^ 2)/(k ^ 2 - t ^ 2) : (t/(k - 1)) = (k - t) ^ 2/(k ^ 2 - t ^ 2) * (k - 1)/t = (k - t)/(k + t) * (k - 1)/t.
Автор:
leilar6plДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть